Effects of vertex insertion on local rescheduling in wireless sensor networks. (2018) - Yang, Chun-Hao; Ssu, Kuo-Feng; Wang, Chao
Rescheduling has abundant issues yet to be explored. The local rescheduling problem in wireless sensor networks (WSNs) have been firstly addressed and investigated in this paper. The algorithms of local rescheduling have been proposed and evaluates the performance of reschedule solutions with different metrics. The solutions have to be under the limitation that the network should stay connected after the process of rescheduling. This paper introduces a theoretical bound of maximum degree after node insertion. Along with empirical results in real world settings, the results motivate the design of algorithms and give possible reasons why existing rescheduling algorithms do not work efficiently. Two local link rescheduling algorithms and one local broadcast rescheduling algorithm are developed as improvements. With different node densities and other critical parameters, simulations show that the developed algorithms greatly improve the ratio of finding proper solutions successfully in both types of scheduling compared with other existing simple algorithms.